A Systematic Review of Preservice Science Teachers' Experience of Problem-Based Learning and Implementing It in the Classroom - Adewale Magaji; Michael Adjani; Samuel Coombes (MDPI AG, 2024)
This study investigates whether problem-based learning (PBL) is used in preservice science teachers' education, how it develops their pedagogical approach, and what they understand about PBL and its implementation in the classroom. The study utilized a systematic review of the related literature in the field of PBL, with a focus on preservice science teachers' education. It used a specific search strategy to identify the literature following the inclusion and exclusion criteria, adhering to the PRISMA guidance and generating a flow diagram. In addition, the Mixed-Methods Appraisal Tool was used to appraise the quality of the articles. The results show that PBL is not fully utilized in preservice science teachers' training and just a few relevant articles have been published in this area. The study reveals that PBL is an effective pedagogical approach in teaching and learning and preservice science teachers should be engaged in the process of learning by taking part in the PBL design process and experiencing it in the classroom as students of their instructors to learn from the process. Continuing professional development would help preservice science teachers to develop the knowledge and skills to design and implement PBL in their classrooms.